Hardness and Electric Dipole Polarizability - Tondon, Asha (Asian Journal of Chemistry, 2010)
Pearson, in 1963, classified the Lewis acids and bases in terms of "hardness". A less polarizable species is hard and more polarizable is soft This proved to be quite successful in rationalizing a variety of chemical observations, especially the exchange reactions. In the present work, a relation between hardness and polarizability has been found, which is further used to calculate the electronegativity of various atoms. It is interesting to note that these calculated values are very close to the experimental values. Further the electrostatic potentials of various atoms have been calculated and compared with the experimental values for better agreement.